The Q loops of the human multidrug resistance transporter ABCB1 are necessary to couple drug binding to the ATP catalytic cycle. Issue 10 (11th July 2014) - Zolnerciks, Joseph K.; Akkaya, Begum G.; Snippe, Marjolein; Chiba, Peter; Seelig, Anna; Linton, Kenneth J.
Abstract : For a primary active pump, such as the human ATP‐binding‐cassette (ABC) transporter ABCB1, coupling of drug‐binding by the two transmembrane domains (TMDs) to the ATP catalytic cycle of the two nucleotide‐binding domains (NBDs) is fundamental to the transport mechanism, but is poorly understood at the biochemical level. Structure data suggest that signals are transduced through intracellular loops of the TMDs that slot into grooves on the NBDs. At the base of these grooves is the Q loop. We therefore mutated the eponymous glutamine in one or both NBD Q loops and measured the effect on conformation and function by using a conformation‐sensitive antibody (UIC2) and a fluorescent drug (Bodipy‐verapamil), respectively. We showed that the double mutant is trapped in the inward‐open state, which binds the drug, but cannot couple to the ATPase cycle. Our data also describe marked redundancy within the transport mechanism, because single‐Q‐loop mutants are functional for Bodipy‐verapamil transport. This result allowed us to elucidate transduction pathways from twin drug‐binding cavities to the Q loops using point mutations to favor one cavity over the other. Together, the data show that the Q loop is the central flexion point where the aspect of the drug‐binding cavities is coupled to the ATP catalytic cycle.—Zolnerciks, J. K., Akkaya, B. G., Snippe, M., Chiba, P., Seelig, A., Linton, K. J., The Q loops of the human multidrug resistance transporter ABCB1 are necessary to couple drug binding to the ATP catalytic cycle. FASEB J. 28, 4335–4346 (2014). www.fasebj.org